2022
DOI: 10.1016/j.amjcard.2021.12.022
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Iron Status to Prognosis After Acute Coronary Syndrome

Abstract: Iron deficiency has been extensively researched and is associated with adverse outcomes in heart failure. However, to our knowledge, the temporal evolution of iron status has not been previously investigated in patients with acute coronary syndrome (ACS). Therefore, we aimed to explore the temporal pattern of repeatedly measured iron, ferritin, transferrin, and transferrin saturation (TSAT) in relation to prognosis post-ACS. BIOMArCS (BIOMarker study to identify the Acute risk of a Coronary Syndrome) is a pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Iron deficiency is a frequent comorbidity in patients with chronic HF, leading to a decreased quality of life and worse overall clinical prognosis [ 8 ]. A cohort study investigated the prognostic relevance of biomarkers of iron status after an ACS by performing high-frequency blood sampling (a median of 17 determinations) in 844 patients over a one-year follow-up period [ 9 ]. The study revealed a higher incidence of the composite outcome of CV mortality and recurrent nonfatal ACS with decreasing log-iron, as well as with decreasing log-TSAT (transferrin saturation).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Iron deficiency is a frequent comorbidity in patients with chronic HF, leading to a decreased quality of life and worse overall clinical prognosis [ 8 ]. A cohort study investigated the prognostic relevance of biomarkers of iron status after an ACS by performing high-frequency blood sampling (a median of 17 determinations) in 844 patients over a one-year follow-up period [ 9 ]. The study revealed a higher incidence of the composite outcome of CV mortality and recurrent nonfatal ACS with decreasing log-iron, as well as with decreasing log-TSAT (transferrin saturation).…”
Section: Resultsmentioning
confidence: 99%
“…The study revealed a higher incidence of the composite outcome of CV mortality and recurrent nonfatal ACS with decreasing log-iron, as well as with decreasing log-TSAT (transferrin saturation). However, no associations with the composite outcome were recorded for ferritin and transferrin [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in the setting of atherosclerosis and coronary syndromes, iron may have a pivotal role. It is involved in oxidative stress, low-density lipoprotein (LDL) oxidation and inflammation [150]. Meng et al [151] reported that reduced circulating iron values were a predictor of coronary atherosclerosis.…”
Section: Ironmentioning
confidence: 99%
“… 11 Higher iron parameters may protect against incident coronary heart disease, 12 whereas iron deficiency predicts poor outcomes after coronary artery events. 13 , 14 , 15 …”
mentioning
confidence: 99%